2017
DOI: 10.1016/j.ensci.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Can suitable candidates for levodopa/carbidopa intestinal gel therapy be identified using current evidence?

Abstract: Advanced Parkinson's disease (APD) is characterized by increased functional disability, caused by motor complications, the presence of axial symptoms, and emergent disease- and drug-related non-motor symptoms. One of the advanced therapies available is intrajejunal infusion of levodopa/carbidopa intestinal gel (LCIG); however, patient selection for this treatment is sometimes difficult, particularly because of overlapping indications with other alternatives.In recent years, strong evidence has supported the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 109 publications
(386 reference statements)
1
23
0
1
Order By: Relevance
“…[ 9 ] The result was that patients showed statistically significant ( P < .05) higher performances in activities of daily living, statistically significant ( P < .001) lower incidence and severity of motor fluctuations, as rating by UPDRS part IV, compared to their best oral therapy and the success rate for PEG-J placement was 100%. [ 9 ] Previous research found that continuous intrajejunal infusion of LCIG provide a significant clinical improvement and improves UPDRS, [ 10 13 ] a result similar to ours. However, device and procedural complications, while generally of mild severity, were present and were explained by the severity and progression of the disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[ 9 ] The result was that patients showed statistically significant ( P < .05) higher performances in activities of daily living, statistically significant ( P < .001) lower incidence and severity of motor fluctuations, as rating by UPDRS part IV, compared to their best oral therapy and the success rate for PEG-J placement was 100%. [ 9 ] Previous research found that continuous intrajejunal infusion of LCIG provide a significant clinical improvement and improves UPDRS, [ 10 13 ] a result similar to ours. However, device and procedural complications, while generally of mild severity, were present and were explained by the severity and progression of the disease.…”
Section: Discussionsupporting
confidence: 86%
“…However, device and procedural complications, while generally of mild severity, were present and were explained by the severity and progression of the disease. [ 10 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although some l ‐dopa unresponsive axial symptoms are not mandatory exclusion criteria for LCIG treatment initiation, clinicians should take into account that a milder axial response to l ‐dopa at baseline implies a worse outcome in terms of FOG and a lower independency in ADLs at long‐term FU. Patients’ selection for LCIG treatment can be challenging, and the identification of the “best candidate” or the “optimal timing” is still a matter of debate . No strong evidences actually support the indication of LCIG treatment starting at the beginning of the advanced phase or its possible disease‐modifying effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LCIG does not seem to accelerate cognitive deterioration, and no significant differences in the long-term cognitive decline were reported in comparison with DBS or oral medical treatment [21]. Finally, amelioration of depression, anxiety, impulse control disorder, and psychosis has also been reported [20].…”
Section: Parkinson's Disease: Therapies Of the Advanced Phase And Rolmentioning
confidence: 97%
“…Nevertheless, the patient's cognitive status has to be carefully evaluated. In fact, due to the gastrostomy and device management, the presence of severe cognitive impairment could unbalance the risk/benefit profile toward lower efficacy and higher prevalence of complications and side effects [20]. For the same reason, the presence of a caregiver is strongly recommended in patients with mild to moderate cognitive impairment undergoing LCIG treatment.…”
Section: Parkinson's Disease: Therapies Of the Advanced Phase And Rolmentioning
confidence: 99%